Deposit reduction in a high pour point oil reservoir due to the activity of indigenous bacterial communities. (May 2016) - He, Yanlong; Zhang, Fan; Banat, Ibrahim M.; Pu, Chunsheng; Dong, Hao; Shu, Fuchang; Shi, Quan; She, Yuehui
Abstract: Physical simulation experiments were performed to simulate the reservoir environment and evaluate deposit reduction and oil recovery by indigenous bacteria inhabiting different types of water. The bacterial communities in the samples were identified based on 16S rRNA gene amplicons. Activation resulted in the predominance of Bacillus sp. and Clostridium ultunense in the samples. The oil was investigated before and after stimulation using the GC, GC–MS and ESI FT-ICR MS techniques to evaluate and analyse the deposit reduction on different scales. The n-alkanes (n > 25) in the sample obtained from the physical simulation experiment using production fluid containing nutrients showed a 68.66% reduction, whereas the amount of wax decreased from 46.27% to 38.75%. Additionally, naphthalene and its homologues decreased by approximately 34.0%. The typical polar compounds containing N1, O1 and O2 class compounds also significantly changed, indicating a marked biodegradation of the alkyl side chains of polar compounds and the pathway of wax metabolism by indigenous bacterium indirectly. The indigenous bacteria in the production fluid more effectively degraded the wax and heavy components. Bacteria such as Acinetobacter sp., Pseudomonas sp. and Bacillus sp. played important roles in deposit reduction and were beneficial to the EOR. Abstract : Highlights: The indigenous bacteria of high pour-point oil reservoir are significantly different to other types of reservoirs. The differences of indigenous bacterial communities in injection water and produced fluids are due to the water treatment. Bacteria such as Acinetobacter sp., Pseudomonas sp. and Bacillus sp. play an important role in deposits reduction. ESI-FT-ICR MS showed the differences between the polar compounds within the deposits before and after microbial flooding. Deposits in high pour-point oil reservoir were significantly reduced due to the activity of indigenous bacteria.